2017
DOI: 10.15517/rbt.v66i1.29502
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuación poblacional de Schistocerca piceifrons piceifrons (Orthoptera: Acrididae) en la Península de Yucatán y su relación con las condiciones climáticas:

Abstract: Abstract:The Central American Locust Schistocerca piceifrons piceifrons is one of the most damaging plant pest in Mexico and Central America. The present work was carried out to evaluate the seasonal population fluctuation of S. p. piceifrons and vegetation diversity and their association with weather factors and edaphic conditions in the gregarious zone of the Yucatán Península. The study was performed in seven sites during three seasons: North-wind (December 2013), rainy (June 2014) and dry (April 2014). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This plant potentially drives aggregation by concentrating locust densities (Poot-Pech et al, 2016;Cullen et al, 2017). Research on the environmental drivers of locust density in the Yucatán peninsula demonstrated a correlation between locust density and the presence of the grass Panicum maximum, but no correlation with soil type (Poot-Pech et al, 2018).…”
Section: Schistocerca Piceifrons Peruviana (Lynchmentioning
confidence: 99%
“…This plant potentially drives aggregation by concentrating locust densities (Poot-Pech et al, 2016;Cullen et al, 2017). Research on the environmental drivers of locust density in the Yucatán peninsula demonstrated a correlation between locust density and the presence of the grass Panicum maximum, but no correlation with soil type (Poot-Pech et al, 2018).…”
Section: Schistocerca Piceifrons Peruviana (Lynchmentioning
confidence: 99%